The Violence against Women and Domestic Violence and the right to liberty and security of person: N.A - Qosaj Mustafa, Ariana; Netkova, Bistra (Advances in Social Sciences Research Journal, 2021)
International human rights instruments specifically dealing with protection of women from violence, include the UN Convention on Elimination of All Forms of Discrimination against Women (CEDAW) and the Council of Europe Convention on protection from violence against women and domestic violence (Istanbul Convention), provide enhanced protection for women from all forms of mental and physical violence and maltreatment. These conventions pose international obligations to state parties to protect the rights of women that are victims of violence including the right to security of person. With respect to violence against women, the article analyses the scope of application of the right to liberty and security of person, by discussing also the possibility of the use of the right of security of persons to the action of other individuals with respect to violence against women, in particularly the state obligations related to domestic violence.